2018
DOI: 10.1111/bjdp.12247
|View full text |Cite
|
Sign up to set email alerts
|

Consider the source: Children link the accuracy of text‐based sources to the accuracy of the author

Abstract: The present research investigated whether young children link the accuracy of text-based information to the accuracy of its author. Across three experiments, three- and four-year-olds (N = 231) received information about object labels from accurate and inaccurate sources who provided information both in text and verbally. Of primary interest was whether young children would selectively rely on information provided by more accurate sources, regardless of the form in which the information was communicated. Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
(41 reference statements)
0
4
0
1
Order By: Relevance
“…For example, Fedra & Schmidt ( 2019 ) found that 3- and 4-year-olds rejected knowledge from a communicator who lacked perceptual access and accepted claims from another who had visual access to the target object. In addition, children are more trusting of claims made by informants with relevant, as opposed to irrelevant, expertise (Boseovski & Thurman, 2014 ; Koenig & Harris, 2005 ; Koenig & Jaswal, 2011 ; Kushnir et al ., 2013 ; Lane & Harris, 2015 ; Lucas et al ., 2017 ; Vanderbilt et al ., 2018 ;). For example, Kushnir et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Fedra & Schmidt ( 2019 ) found that 3- and 4-year-olds rejected knowledge from a communicator who lacked perceptual access and accepted claims from another who had visual access to the target object. In addition, children are more trusting of claims made by informants with relevant, as opposed to irrelevant, expertise (Boseovski & Thurman, 2014 ; Koenig & Harris, 2005 ; Koenig & Jaswal, 2011 ; Kushnir et al ., 2013 ; Lane & Harris, 2015 ; Lucas et al ., 2017 ; Vanderbilt et al ., 2018 ;). For example, Kushnir et al .…”
Section: Resultsmentioning
confidence: 99%
“…Past accuracy refers to a history of making accurate claims or good performances in tasks. It was found that children can track an informant’s record of past accuracy and use it as a cue to current reliability across experimental variations (Barth et al ., 2014 ; Brink & Wellman, 2020 ; Brosseau-Liard et al ., 2015 ; Corriveau et al , 2011 ; Gweon et al ., 2014 ; Kushnir & Koenig, 2017 ; Li & Yow, 2018 ; Liu et al ., 2013 ; Pasquini et al ., 2007 ; Poulin-Dubois & Chow, 2009 ; Ronfard & Lane, 2018 ; Vanderbilt et al , 2018 ). For example, Poulin-Dubois and Chow ( 2009 ) found that 16-month-old infants were able to encode and recall the accuracy and inaccuracy of adults’ searching behaviors in a task, and this record influenced how much attention the infants paid to those adults’ searching behaviors in a subsequent task.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Children have access to a variety of non-human information sources such as text-based sources of information (e.g., small information cards; Corriveau et al, 2014;Einav et al, 2013;Einav et al, 2018;Eyden, et al, 2013;Robinson et al, 2013), the Internet or search engines (Einav et al, 2020;, books (Vanderbilt, Ochoa, & Heilbrun, 2018). and even artificial intelligences including voice assistants (e.g., Siri or Alexa), humanoid robots, or computer informants (Danovitch & Alzahabi, 2013;Lovato, 2019;Lovato & Piper, 2019).…”
Section: Defining and Framing Knowledge Artifactsmentioning
confidence: 99%
“…Em resposta à primeira pergunta levantada nessa revisão sobre o desenvolvimento da confiança seletiva nos anos pré-escolares, os artigos, em conjunto, revelam que as crianças de três anos já são capazes de rastrear o histórico de acurácia de informantes e esse rastreamento não depende da forma como a informação é veiculada (e.g., informação oral ou escrita; Vanderbilt, Ochoa, & Heilbrun, 2018). Na mesma idade, elas também já são capazes de discriminar um informante com más intenções de outro que tem boas intenções (Mascaro & Sperber, 2009).…”
Section: Considerações Finaisunclassified